Near things: leisure time and rest. Phenomenology of idleness in Friedrich Nietzsche - Scolari, Paolo (Voluntas: Revista Internacional de Filosofia, 2022)
Nietzsche was aware of the importance of living in the moment; both outdated and a product of his times, he tells us plainly not to be a John-a-dreams, to look around and see clearly how men live each day. In his slighting, plain-spoken judgements and his impassioned polemics, Nietzsche constantly shows how attentive an observer he is of the reality and problems of his time; it is difficult to find a topic on which he has not expressed his opinion. His attention rests on those small themes that make up the rhapsodic existence, public and private, of those who live in modern society, all small realities which, as Nietzsche himself observes, are very badly observed by most people and very rarely given much attention by a philosophy that is still too far-removed and detached from the reality of everyday life, an abstract, academic philosophizing that is hypocritically interested only in the most important things and the great questions but inevitably ends up with the neglect of what is human. Nietzsche, on the other hand, believes he has a keen eye for the smallest and most everyday things, and always succeeds in the difficult enterprise of viewing the familiar as a problem. These near things also include leisure time and rest.